2016
DOI: 10.7120/09627286.25.1.021
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of veterinary students in Croatia toward farm animal welfare

Abstract: This survey was undertaken to assess the attitudes of Croatian veterinary students regarding farm animal welfare issues. The study included students of all undergraduate years at the only Faculty of Veterinary Medicine in Croatia. First-year students were surveyed twice, ie before and after attending the course on animal welfare, using a written questionnaire containing statements with a five-point Likert scale for choice of answers. Students consider good animal welfare necessary for sustainability of farming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 20 publications
4
23
0
Order By: Relevance
“…The results concerning cattle contradicted the findings of the DG SANTE study (2016) where students from other faculties were only moderately concerned by this species. It is possible that the different perception of veterinary students toward cattle welfare is due to the longer time that the students spend on a cattle farm as compared, for example, to a chicken farm, as also suggested by Ostović and others (2016). For this reason, cows are probably perceived as being more sentient than other species (Paul and Podberscek 2000, Levine and others 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The results concerning cattle contradicted the findings of the DG SANTE study (2016) where students from other faculties were only moderately concerned by this species. It is possible that the different perception of veterinary students toward cattle welfare is due to the longer time that the students spend on a cattle farm as compared, for example, to a chicken farm, as also suggested by Ostović and others (2016). For this reason, cows are probably perceived as being more sentient than other species (Paul and Podberscek 2000, Levine and others 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Students of all six study years had the same curriculum on animal welfare. The survey was voluntary, anonymous and approved by the institutional Board for Quality Management (for details, see Ostović et al [12]).…”
Section: Participants/samplementioning
confidence: 99%
“…These statements were in the forms of five-point Likert scale questions (1 = fully disagree, 2 = disagree, 3 = neutral/unsure, 4 = agree, and 5 = fully agree), Yes/No/I do not know questions, and ratio scale questions. The questionnaire was pre-tested [12], with reliability (α) of 0.683.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the gender has been repeatedly found to impact on the empathy toward animals, with women being more empathetic to non-human animals and obtaining higher scores in the Animal Attitude Scale (Herzog et al, 1990;Mazas et al, 2013;Herzog, 2015). In the field of veterinary medicine, both students (Serpell, 2005) and professionals (Ostović et al, 2016;Colombo et al, 2017) were found to be influenced in their attitude toward non-human animals by factors such as the gender and previous experiences with animals. However, until now veterinarians have been investigated as a whole professional category, and scant attention has been reserved to the category of veterinarians who are mostly involved in the assessment of pet behaviour and welfare.…”
Section: Discussionmentioning
confidence: 99%